Problematic diagnosis of economic development of textile enterprises - Shikovets, Catherine (Technium EconomiA, 2024)
The global financial crisis has shown that the old economic models for diagnosing the economic development of enterprises do not work with the necessary efficiency. Today, they have lost their relevance due to changes in economic systems and economic relations between them. Therefore, the problem of developing such models, methods and forms of assessing economic development, which would best meet the requirements of today, is acute. The paper considers the problematic diagnosis of economic development of textile enterprises. Since economic development is a system-driven development, the basis of its manageability is a systematic approach, and modern information technology, which allows quickly modeling of different options for development, it is proposed to apply the "Cybernetic concept of management in the space of boundary resources and states of the object of development” (CURSOR+) to the problematic diagnosis of the development of textile enterprises. As a result, an integrated model of system-situational development and a balanced scorecard (BSC) is proposed. The causal relationships that exist between all four indicators of the BSC are a reflection of the business strategy adopted by the enterprise. Such correlations are assessed using a correlation coefficient. To obtain a single diagnostic indicator of development, it is proposed to carry out the procedure of convolution of all correlation coefficients. The analysis of necessary and sufficient conditions for the existence of the extremum of the development indicator as a function of many variables allowed determining the differential levels of economic development of textile enterprises.